PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA GAMBAR DI KELAS V SD NEGERI 21 KOTO TUO KABUPATEN AGAM - Salsabilla Suci Rahayyu; elfia sukma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the lack of poetry writing skills in class V SDN 21 Koto Tuo Agam district. This is because teachers have not used effective learning models and media in the learning process of writing poetry. This study aims to describe the improvement of poetry writing skills using the Problem Based Learning (PBL) model assisted by image media in Class V SDN 21 Koto Tuo Agam Regency This research is a class action research (PTK) with qualitative and quantitative approaches. Implemented in 2 cycles, cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. Each cycle has stages of planning, implementation, observation and reflection. The subjects of this study were teachers and students in class V as many as 20 people. Research data obtained from the Teaching Module assessment, implementation process and learning outcomes. The data collection techniques used were observation, tests and non-tests. The results showed an increase in cycle I teaching module aspects obtained an average of 90.58% (B) then increased in cycle II 95.83% (SB). Implementation of cycle I on the aspect of teacher activity obtained an average of 85.71% (B) and increased in cycle II to 96.28% (SB). Implementation of cycle I in the aspect of learner activity obtained an average of 87.49% (B) and increased in cycle II to 96.28% (SB). The learning outcomes of students in cycle I obtained an average of 75.68 (C), increasing in cycle II to 88.63 (B). It can be concluded that the Problem Based Learning (PBL) model assisted by image media can improve poetry writing skills in Indonesian language learning.